2018
DOI: 10.1186/s13045-018-0554-z
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion-mediated mitochondria transfer contributes to mesenchymal stem cell-induced chemoresistance on T cell acute lymphoblastic leukemia cells

Abstract: BackgroundDespite the high cure rate of T cell acute lymphoblastic leukemia (T-ALL), drug resistance to chemotherapy remains a significant clinical problem. Bone marrow mesenchymal stem cells (MSCs) protect leukemic cells from chemotherapy, but the underlying mechanisms are poorly understood. In this study, we aimed to uncover the mechanism of MSC-induced chemoresistance in T-ALL cells, thus providing a promising clinical therapy target.MethodsCell viability was determined using the viability assay kit CCK-8. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
162
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(174 citation statements)
references
References 67 publications
1
162
2
Order By: Relevance
“…In this work, we assemble direct evidence for a reproducible, rapid, dose-dependent, and efficient MitoT from cultured MSCs to T and B lymphocytes isolated from healthy donors. In contrast with our results, Wang et al [15] showed that while both ALL T cells and Jurkat cells can transfer MT to MSCs, they receive almost no MT from MSCs, resulting in chemoresistance. The suppression of MitoT at 4°C and the detection of only human-specific mitochondrial genes (qPCR) but no human b2microglobulin genes in murine UC-MSC-co-cultured murine lymphoid cells confirmed the mediation of an energy-dependent ª 2020 The Authors EMBO reports 21: e48052 | 2020 process, not attributable to cell fusion nor dye-related artifact.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this work, we assemble direct evidence for a reproducible, rapid, dose-dependent, and efficient MitoT from cultured MSCs to T and B lymphocytes isolated from healthy donors. In contrast with our results, Wang et al [15] showed that while both ALL T cells and Jurkat cells can transfer MT to MSCs, they receive almost no MT from MSCs, resulting in chemoresistance. The suppression of MitoT at 4°C and the detection of only human-specific mitochondrial genes (qPCR) but no human b2microglobulin genes in murine UC-MSC-co-cultured murine lymphoid cells confirmed the mediation of an energy-dependent ª 2020 The Authors EMBO reports 21: e48052 | 2020 process, not attributable to cell fusion nor dye-related artifact.…”
Section: Discussioncontrasting
confidence: 99%
“…While most of the work regarding mitochondrial delivery from one cell to another involves the rescue of damaged cells by healthy ones, no study to date has shown the physiological or artificial transfer to healthy lymphocytes. In this regard, a recent study described MT transfer mediated by the adhesion molecule ICAM-1 between Jurkat cells and MSCs, where treatment with a neutralizing antibody against ICAM-1 led to partial inhibition of MitoT [15]. Since MitoTracker-labeled MT can leak dye over time, control experiments were necessary to confirm the real uptake of MT.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of mitophagy negated the cytoprotective effects of MSCs in other somatic cells, which suggests that MSC sensing of damaged mitochondria may mediate their therapeutic responses 53 . Supporting this, the cell contact‐dependent transfer of mitochondria from chemotherapy‐treated T lymphocytes to MSCs was also determined to be critical to their ability to decrease mitochondrial O 2 .− production and cell death in T lymphocytes 120 . Nonetheless, in this study, mitochondrial transfer appeared to be predominately unidirectional and very few MSC‐derived mitochondria were observed in T cells.…”
Section: Antioxidative Mechanisms Of Mscsmentioning
confidence: 94%
“…Thus, tigecycline, a broad‐spectrum antibiotic, which reduces biogenesis of mitochondria by causing energy crisis and enhanced ROS production, was shown to be a strong and selective (vs. healthy counterpart cells) suppressor of leukemic cells, in particular, ALL . Recently, Wang and coworkers demonstrated a very peculiar tactics of T‐ALL cells, which were able to preferentially export their mitochondria to stromal cells via nanotubes, thus, preventing the excessive mitoROS production in source cells in a response to chemotherapy . In general, a protective role of stromal cells is a very essential factor for chemoresistance and needs to be considered and targeted in anticancer treatments trials.…”
Section: Targeting Mitochondria In Therapy Of T‐allmentioning
confidence: 99%
“…112 Recently, Wang and coworkers demonstrated a very peculiar tactics of T-ALL cells, which were able to preferentially export their mitochondria to stromal cells via nanotubes, thus, preventing the excessive mitoROS production in source cells in a response to chemotherapy. 113 In general, a protective role of stromal cells is a very essential factor for chemoresistance and needs to be considered and targeted in anticancer treatments trials.…”
Section: Antioxidant Suppression or Ros Induction Mitocans Targetingmentioning
confidence: 99%